Exosomes as Theranostic Targets: Implications for the Clinical Prognosis of Aggressive Cancers - Gulati, Richa; Nandi, Dhruva; Sarkar, Koustav; Venkataraman, P.; Ramkumar, K. M.; Ranjan, Priya; Janardhanan, Rajiv (Frontiers in Molecular Biosciences, 2022)
Exosomes are extracellular vesicles produced by a diverse range of cell types and extensively distributed in physiological fluids. Because of their significant role towards progression of cancer, they have been a focal point for the novel cancer therapy approach. Exosomes are highly efficient at transporting proteins, RNAs and small drugs into cancer cells for therapeutic purposes. Adding to their prominent role as potential biomarkers for transporting targeted information from their progenitor cells, exosomes have also emerged as a new avenue for the development of more effective clinical diagnostics and therapeutic techniques, also known as exosome theranostics. Lipids, proteins, and nucleic acids transported by exosomes were investigated as potential biomarkers for cancer diagnosis, prognosis, as well as future cancer treatment targets. The unique mechanism of exosomes, as well as their therapeutic and diagnostic uses, also known as theranostic applications of exosomes in malignancies, are discussed in this review.